Still Different? Income Distribution in the Nordic Countries in a European Comparison - Johan Fritzell (Luxembourg Income Study (LIS), 2000)
A bottom-line of the interest in welfare state programs and cross-national variations in the pattern, size and structure of various social policies, is that we expect that the welfare state is an institution that greatly affects our lives and well-being. A further assumption is that this impact differs between individuals and social categories, and accordingly that the degree of inequality in the distribution of societal goods and resources has a scope to be affected. Hence, in so far as there is cross-national variation in these programs, 'outcome' inequality may systematically vary across nations. It has been said that one characteristic of the Nordic welfare states is that they pursue a different conception of equality, with a particular strong focus on equality of result (or outcome), as opposed to different equality of opportunity or different equity conceptions (for a discussion see e.g. Esping-Andersen 1996). This Chapter aims at looking at a central outcome in this respect, namely economic resources or to be more precise the distribution of annual income. The overarching question raised in this Chapter concerns whether or not we still find prove of a specific Nordic model when we from a variety of perspectives look at the distribution of income and compare the outcomes with that prevailing in three other European countries. Do we find any evidence on convergence, divergence or similar trends? Within this general issue four types of questions are raised and analyses on each of them will be conducted. The first issue raised concerns the level of inequality. Are the Nordic countries still in the mid1990s really that different from other European countries in terms of overall income inequality? Second, to what extent do we find commonality and variation with regard to recent changes in inequality? Do we find any evidence for a convergence with respect to the degree of inequality? Third, what is the role of cash benefits of welfare states in the income distribution process? This will be studied by comparing the size and distributional profile of income transfers and by comparing the extent of inequality when comparing before and after cash benefits is taken into account. Fourth, to what extent do we find cross-national similarity and variation with regard to the relative income position and poverty risks for more specific social categories when comparing their situation in the mid90s with that prevailing about a decade before? Is it still the case that specific vulnerable groups fare relatively better in the Nordic countries as indicated by earlier research?
Keywords: 330; Einkommensverteilung; Sozialstaat; Vergleich; Nordeuropa; Deutschland; Großbritannien; Niederlande